2008
DOI: 10.1007/s11948-008-9074-5
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and Research Misconduct: An Analysis of Research Mentoring in Closed ORI Cases

Abstract: We are reporting on how involved the mentor was in promoting responsible research in cases of research misconduct. We reviewed the USPHS misconduct files of the Office of Research Integrity. These files are created by Institutions who prosecute a case of possible research misconduct; ORI has oversight review of these investigations. We explored the role of the mentor in the cases of trainee research misconduct on three specific behaviors that we believe mentors should perform with their trainee: (1) review sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 6 publications
0
61
0
Order By: Relevance
“…Many trainee missteps can be traced to a fear of failure and a lack of quality mentorship. One study 7 of trainees who were found guilty of misconduct revealed that 62% of their mentors had not established adequate procedures, such as providing clear rules on data ownership and recording, safety, materials transfer or scheduling regular meetings, and 73% had not reviewed trainees' raw data. A survey 8 at a major US cancer centre found that nearly one-third of 140 trainees felt pressure to "prove" a mentor's hypothesis, even though results did not support it.…”
Section: Targeted Remediesmentioning
confidence: 99%
“…Many trainee missteps can be traced to a fear of failure and a lack of quality mentorship. One study 7 of trainees who were found guilty of misconduct revealed that 62% of their mentors had not established adequate procedures, such as providing clear rules on data ownership and recording, safety, materials transfer or scheduling regular meetings, and 73% had not reviewed trainees' raw data. A survey 8 at a major US cancer centre found that nearly one-third of 140 trainees felt pressure to "prove" a mentor's hypothesis, even though results did not support it.…”
Section: Targeted Remediesmentioning
confidence: 99%
“…To illustrate the importance of mentorship, an example is given of another study conducted by the US ORI on the role played by mentors in cases of trainee research misconduct. It was found that 73% of mentors/supervisors had not looked at the primary data generated by their trainees; 62% had little appreciation of the conduct of research they were presumably supervising and had not set adequate supervisory standards for their mentees, such as maintaining laboratory notebooks; and mentors seemed to pay little attention to mentees' reports because of high stress levels 27 . Therefore institutional leaders need to play a more active role with researchers to build institutional programs that teach mentors how to mentor.…”
Section: Education Training and Mentorshipmentioning
confidence: 99%
“…Therefore institutional leaders need to play a more active role with researchers to build institutional programs that teach mentors how to mentor. In order to reduce the incidence of trainee misconduct or reduce its impact, mentors must ensure that they regularly review trainee raw/primary data as a preventive strategy of reducing opportunities for trainee misconduct; set appropriate standards, rules and procedures for collecting, recording and maintaining data, and ensure that they are implemented and enforced; and pay more attention to potential stressors that might significantly affect the performance of their trainees 27 .…”
Section: Education Training and Mentorshipmentioning
confidence: 99%
“…Some authors have felt that mentors should display high ethical standards in their own conduct of research and set examples for trainees to follow. Behavior of the mentors provides nonverbal cues that act as informal education of the trainees (Pellegrino, 1992;Wocial, 1995;Wright et al, 2008). More empirical research is required to assess whether mentoring improves the ethical behavior of the mentees.…”
Section: Primary Prevention Models "Person Approach" To Primary Prevementioning
confidence: 99%